Deteksi Serangan pada Jaringan IoT Menggunakan Seleksi Fitur Gabungan dan Optimasi Bayesian - Samsudiat; Kalamullah Ramli (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
Machine learning (ML)-based attack detection is a promising alternative for addressing cybersecurity threats in Internet of things (IoT) networks. This approach can handle various emerging attack types. However, the growing volume of data and the reliance on default parameter values in ML algorithms have led to performance degradation. This study proposed a hybrid feature selection method combined with Bayesian optimization to improve the effectiveness and efficiency of attack detection models. The hybrid feature selection method integrated correlation-based filtering, which aimed to rapidly remove highly correlated features, and feature importance, which aimed to select the most influential features for the model. In addition, Bayesian optimization was employed to efficiently identify the optimal parameter values for lightweight and robust ML algorithms suitable for IoT networks, namely decision tree and random forest. The constructed model was then evaluated using the latest attack dataset, CICIoT2023, which consists of seven types of attacks: DDoS, DoS, Mirai, spoofing, reconnaissance, web-based attacks, and brute force. The evaluation results showed that the hybrid feature selection technique produced a more efficient model compared to several single feature selection methods by selecting 5 out of 46 features. Furthermore, Bayesian optimization successfully identified the optimal parameter values, improving model performance in terms of accuracy, precision, recall, and F1 score up to 99.74%, while reducing computational time by as much as 97.41%. Based on these findings, the proposed attack detection model using hybrid feature selection and Bayesian optimization can serve as a reference for implementing cybersecurity solutions in IoT networks.